Academy of Nutrition and Dietetics complete food and nutrition guide - Duyff, Roberta Larson; Academy of Nutrition and Dietetics (Boston ; New York : Houghton Mifflin Harcourt, 2017)
The choices you make every day about food and nutrition really do matter. They impact your health and well-being now and throughout your life. Duyff provides sound, positive, and practice advice for you and your family, at every age and stage of life.
Introduction -- Wellness: eat smart, get active, live well. Making your food and lifestyle choices count ; Plan smart to eat smart ; Make quick, easy meals and snacks ; Think your drinks -- Food and nutrition: choices in the marketplace. Producing your food ; Shop with nutrition savvy ; Keep your food safe ; Cook for flavor and health ; Eat smart away from home ; Use supplements wisely -- Nutrients: what's inside your food. Carbs: sugars, starches, and fiber ; Protein power ; Fat facts ; Vitamins and minerals ; Water, "phytos," and probiotics -- Food: for every age and every stage. Give your baby a health start ; Help kids grow up healthy ; Manage women's unique nutrition concerns ; Manage men's nutrition issues ; Eat healthy beyond midlife ; Eat smart for sports -- Smart eating: preventing and managing health issues. Reach and maintain your healthy weight ; Cope with food allergies and other food sensitivities ; Manage cardiovascular disease, diabetes, and cancer ; Manage other diet-related health issues -- Resources for healthy eating. Keep "well" informed.
"Completely updated & revised"--Cover.
In English
NBL010825
Keywords: Nutrition -- Popular works; HEALTH & FITNESS / Diet & Nutrition / Nutrition; Nutrition; Popular works